Morphological mutations of patios, from traditional to contemporary housing in Tadjmout city (Algeria): implications and considerations - Chellali, Ali; Khettabi, Latifa (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
This study investigates the morphological transformations of patios in Tadjmout city (Algeria), tracing their evolution from traditional to contemporary housing through a typo-morphological approach at both urban and architectural scales. Thirteen representative houses, distributed across five urban zones reflecting different historical periods, were analysed. Field measurements were redrawn and normalised using computer-aided design tools, while void/solid and height/width ratios were computed for typological comparison, complemented by geometric and pictorial analyses. The results reveal a transition from central, spacious, and horizontally developed patios in traditional houses to lateralised, multipolar, and increasingly vertical voids (light wells) in contemporary dwellings. These transformations indicate a weakening of absolute introversion and a decline in the patio’s structural and distributive roles, driven by socio-economic and spatial constraints. Nevertheless, the patio persists as a symbolic element of local building culture.